2019
DOI: 10.1111/cpf.12606
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of patients undergoing standardized bicycle exercise stress testing: new recommendations for grading of exercise capacity are clinically relevant

Abstract: Summary Introduction A new grading of exercise capacity during bicycle stress testing has been proposed in Sweden based on the new reference material (‘the Kalmar material’), which has not been validated. We aimed to examine the prognostic information of the new grading of exercise capacity during exercise stress testing. Methods Data on all bicycle exercise tests performed at the Department of Clinical Physiology in Kalmar between May 2005 and October 2016 were cross‐linked with the Causes of Death Register (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…This can possibly be explained by the confounding effect of maximum workload (exercise capacity), associated both with higher SBP (via greater cardiac output) 12,14,15 and with better survival. 27,28 Using the workload-indexed SBP response to exercise may circumvent this bias, accounting for both exercise capacity and SBP. 11 Whether the SBP/W-slope or peak SBP/W-ratio provide prognostic value remains to be elucidated, although recent data on the SBP/METslope in males were promising.…”
Section: Rationale For Using Workload-indexed Sbp Measuresmentioning
confidence: 99%
“…This can possibly be explained by the confounding effect of maximum workload (exercise capacity), associated both with higher SBP (via greater cardiac output) 12,14,15 and with better survival. 27,28 Using the workload-indexed SBP response to exercise may circumvent this bias, accounting for both exercise capacity and SBP. 11 Whether the SBP/W-slope or peak SBP/W-ratio provide prognostic value remains to be elucidated, although recent data on the SBP/METslope in males were promising.…”
Section: Rationale For Using Workload-indexed Sbp Measuresmentioning
confidence: 99%
“…In addition, the SBP response (Hedman, et al 2019; Sipila, et al 2019; Tsuda, et al 1993), exercise capacity (Forslund, et al 2000; Myers, et al 2002; Salokari, et al 2019; Sipila, et al 2019) and heart rate recovery (Cole, et al 1999; Sipila, et al 2019) have been shown prognostic of future ACS and mortality. In the same cohort, we have previously shown that exercise capacity is strongly associated with both all‐cause and cardiovascular mortality, as well as hospitalization for ischaemic heart disease and heart failure (Lindow, et al 2019). Thus, despite that exercise stress testing has been shown to have poor diagnostic accuracy regarding obstructive coronary heart disease, using anatomical coronary angiography as reference standard (Knuuti, et al 2018), this study highlights the clinical usefulness of exercise stress testing, especially from a prognostic perspective, but also the importance of not interpreting the test based on the ST response alone.…”
Section: Discussionmentioning
confidence: 81%
“…This study adds to the mountain of evidence of the prognostic information available in exercise stress testing (Cole, et al 1999; Cole & Ellestad, 1978; Daugherty, et al 2011; Forslund, et al 2000; Hedman, et al 2019; Ho, et al 2008; Lindow, et al 2019; Mark, et al 1987; Myers, et al 2002; Salokari, et al 2019; Sipila, et al 2019; Tsuda, et al 1993; Weiner, et al 1984; Weiner, et al 1986). In the most recent guidelines for management of patients with chronic coronary syndrome, exercise stress testing is no longer recommended as the initial diagnostic test in patients with stable chest pain patients (Knuuti, et al 2019).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We performed a consecutive cohort study including patients aged 18 years or older who had performed a clinical bicycle exercise stress test and a resting transthoracic echocardiography within 90 days of the exercise stress test at the Department of Clinical Physiology at Kalmar County Hospital, Sweden, between 31 May 2005 and 31 Oct 2016. The exercise stress test database has been described in detail elsewhere [16][17][18][19]. We excluded those who had an exercise time less than 3 minutes or had atrial fibrillation, considering the challenge of distinguishing aberrantly conducted supraventricular complexes from PVCs.…”
Section: Methodsmentioning
confidence: 99%